Math Trace of a Million Flowers City: Learning Two-Dimensional using Ethno-RME and MathCityMap - Ristiana, Novita; Prahmana, Rully Charitas Indra; Shahrill, Masitah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2024)
Recent research addressing the integration of cultural contexts with digital tools in mathematics education remains scarce. Previous studies have predominantly focused on traditional teaching methods, ethnomathematics, and implementing Realistic Mathematics Education (RME) as distinct approaches. However, this study bridges a critical gap by combining Ethnomathematics and RME, referred to as Ethno-Realistic Mathematics Education (Ethno-RME), with MathCityMap technology. This innovative approach applies culturally relevant mathematics instruction to real-world scenarios. Specifically, the research enhances student engagement with two-dimensional geometric shapes through experiential learning set in the cultural context of Magelang Square in the City of Million Flowers. Employing a design research approach with a validation studies scenario, data were collected via photo and video documentation, interviews, and student worksheets. The study's learning trajectory is structured around three MathCityMap activities, demonstrating that integrating Magelang Square's cultural context with Ethno-RME and MathCityMap technology significantly improves students' conceptual understanding of two-dimensional shapes. These findings provide valuable insights for educators by introducing a novel pedagogical framework emphasizing the importance of cultural relevance and technological integration in mathematics education.